Papiller Tiroid Kanseri - Kahraman, Emir Gökhan (Tiroid Kanserlerine Güncel Yaklaşım, 2024)
Papiller tiroid kanseri, tiroid kanserlerinin en yaygın türüdür ve oldukça tedavi edilebilirdir. Teşhis için fizik muayene, ultrason ve biyopsi kullanılır. Tedavi, hastanın durumuna göre cerrahi, radyoaktif iyot tedavisi ve hormon replasman tedavisini içerebilir. Tedavi sonrası izleme için tiroglobulin ve antitiroglobulin antikoru ölçümleri yapılır. Kitap, özellikle medikal onkolog gözü ile papiller tiroid kanseri tedavisi hakkında bilgi verme amacıyla yazılmıştır. Papillary thyroid cancer is the most common type of thyroid cancer and is highly treatable. Physical examination, ultrasound and bacteria are used for diagnosis. Treatment includes surgery, radioactive therapy, and hormone replacement therapy, depending on the patient's treatment. Thyroglobulin and antithyroglobulin antibody measurements are taken for monitoring after treatment. The book is written with the aim of providing information about the treatment of papillary thyroid cancer, especially from the perspective of a medical oncologist.